Ecklonia cava promotes hair growth. (December 2013) - Bak, S. S.; Ahn, B. N.; Kim, J. A.; Shin, S. H.; Kim, J. C.; Kim, M. K.; Sung, Y. K.; Kim, S. K.
Summary Background Previous studies have reported the protective effects on skin elasticity of the edible marine seaweed Ecklonia cava, which acts through regulation of both antioxidative and anti‐inflammatory responses. Aim We evaluated the effect of E. cava and one of its components, dioxinodehydroeckol, on hair‐shaft growth in cultured human hair follicles and on hair growth in mice. Methods The MTT (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay was used to check cell viability of human dermal papilla cells (DPCs) and outer root sheath (ORS) cells after treatment with E. cava and its metabolite, dioxinodehydroeckol. Hair‐shaft growth was measured using the in vitro hair‐follicle organ‐culture system, in the presence or absence of E. cava and dioxinodehydroeckol. Anagen induction activity was examined by topical application of E. cava to the dorsal skin of C57BL/6 mice. Insulin‐like growth factor (IGF)‐1 expression was measured by reverse transcriptase PCR and ELISA. Results The proliferation activity was found to be highest for the ethyl acetate‐soluble fraction of E. cava (EAFE) in DPCs and in ORS cells. Treatment with EAFE resulted in elongation of the hair shaft in cultured human hair follicles, and promoted transition of the hair cycle from the telogen to the anagen phase in the dorsal skin of C57BL/6 mice. In addition, EAFE induced an increase in IGF‐1 expression in DPCs. Dioxinodehydroeckol, a component of E. cava, induced elongation of the hair shaft, an increase in proliferation of DPCs and ORS cells, and an increase in expression of IGF‐1 in DPCs. Conclusions These results suggest that E. cava containing dioxinodehydroeckol promotes hair growth through stimulation of DPCs and ORS cells.